Information and Temporality - Flender, Christian (Frontiers in Physics, 2016)
Being able to give reasons for what the world is and how it works is one of the defining characteristics of modernity. Mathematical reason and empirical observation brought science and engineering to unprecedented success. However, modernity has reached a post-state where an instrumental view of technology needs revision with reasonable arguments and evidence, i.e., without falling back to superstition and mysticism. Instrumentally, technology bears the potential to ease and to harm. Easing and harming can't be controlled like the initial development of technology is a controlled exercise for a specific, mostly easing purpose. Therefore, a revised understanding of information technology is proposed based upon mathematical concepts and intuitions as developed in quantum mechanics. Quantum mechanics offers unequaled opportunities because it raises foundational questions in a precise form. Beyond instrumentalism it enables to raise the question of essences as that what remains through time what it is. The essence of information technology is acausality. The time of acausality is temporality. Temporality is not a concept or a category. It is not epistemological. As an existential and thus more comprehensive and fundamental than a concept or a category temporality is ontological; it does not simply have ontic properties. Rather it exhibits general essences. Datability, significance, spannedness and openness are general essences of equiprimordial time (temporality).